Self-perceived listening comprehension strategies used by Iranian EFL students - Nowrouzi, Sara; Tam, Shu Sim; Zareian, Gholamreza; Nimehchisalem, Vahid (Australian International Academic Centre, 2014)
Numerous studies are available on L2 learners’ strategy use; however, there is no study investigating the Iranian tertiary level EFL learners’ listening strategy use. The present paper reports the findings of a cross-sectional study that explored a group of Iranian EFL learners’ (n = 100) use of listening comprehension strategies. The instrument that was used for collecting the data was called the Listening Strategy Use Questionnaire (LSUQ) by Nowrouzi, Tam, Nimehchisalem, and Zareian (2014). The instrument divides listening strategies into cognitive, metacognitive, and socio-affective categories. Based on the results, on average the respondents reported low levels of self-perceived use of cognitive, metacognitive, and socio-affective strategies. The results indicate a serious need to focus more on the students’ listening comprehension skills in general and their listening strategies in particular.